2014
DOI: 10.1002/micr.22299
|View full text |Cite
|
Sign up to set email alerts
|

Descending branch of the lateral circumflex femoral artery as a recipient vessel for vascularized fibular grafts: Clinical case series

Abstract: Vascularized fibular grafts (VFG) are used for the treatment of femoral head avascular necrosis, osteomyelitis, nonunions, and excessive bone defects. Mostly the ascending branch of the lateral circumflex femoral artery (LCFA) or first or second perforating branch of the profound femoral artery is used for the customary recipient vessel. In this report, an alternative technique of using descending branch of LCFA in VFG surgery and its clinical results are reported. Sixteen patients (13 men and 3 women) underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The DB of the LCFVs can provide reliable blood supply for free tissue transfer to the knee 15,16. Given its popularity due to most of the surgeon’s experience with the ALT flap, it is often a straightforward dissection for potential alternative use as a recipient vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DB of the LCFVs can provide reliable blood supply for free tissue transfer to the knee 15,16. Given its popularity due to most of the surgeon’s experience with the ALT flap, it is often a straightforward dissection for potential alternative use as a recipient vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The DB of the LCFVs can provide reliable blood supply for free tissue transfer to the knee. 15,16 Given its popularity due to most of the surgeon's experience with the ALT flap, it is often a straightforward dissection for potential alternative use as a re-cipient vessel. The DB in the thigh is versatile when dissected at length to be placed in close proximity to the knee, making it an excellent recipient vessel for free tissue transfer to the knee.…”
Section: Discussionmentioning
confidence: 99%
“…It proceeds downward, while sending perforators to supply the skin and muscles around the anterolateral aspect of the thigh (Figure 2). Usually, the descending branch has an external diameter of more than 2 mm at the proximal end with a pedicle of more than 8 cm in length (Figure 3) [18,19]. When a larger flap is required, more than two perforator arteries should be preserved between the flap and pedicle.…”
Section: Surgical Procedures Of Free Flow-through Alt Flapmentioning
confidence: 99%
“…Whereas the branching patterns of the circumflex femoral arteries have been thoroughly mapped by Vazquez et al () and the clinical anatomy of the medial femoral artery has been reported in detail by Clarke and Colborn (), the variability and clinical anatomy of the DBLCFA itself are mostly unknown and only exceptional case studies have been reported (Goel et al, ). Despite being used successfully as the pedicle of anterolateral thigh flaps or fibular grafts in plastic and reconstructive surgery and orthopedics (Choi et al, ; Gokhan et al, ; Jia et al, ), the DBLCFA is still extremely rarely used for CABG. Despite preliminary studies on its preparation (Loskot et al, ), anatomical and histological studies linked with angiographic assessment of atherosclerosis in patients undergoing CABG are still lacking, and this became the rationale for the present study.…”
Section: Introductionmentioning
confidence: 99%